High-frequency Resonant Voltage Caused by AC Electric Locomotive in the Traction Network and Its Protection - JIANG Jiajiu; CHEN Hanqin; WAN Guang (Kongzhi Yu Xinxi Jishu)
Based on the harmonic source of converter’s modulation voltage of AC electric locomotive, it discussed the generation principles of high frequency resonance voltage of traction network. The system simulations were carried out for AC locomotives with different traction network sections, various chopper frequencies and protection measures for harmonic elimination, from which the variation rule of the traction resonant voltage was obtained. Both ends of the damping filter can effectively eliminate the influence of harmonic voltage. The ideas of protective measures were put forward on the effects of different objects.